Development and Validation of a New Stability Indicating RP-UFLC Method for the Estimation of Ranolazine Tablets - Aluri, Sai Gnaneswari (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Ranolazine is a piperazine derivative used for the treatment of chronic angina (chest pain). It is a new anti-ischemic drug and can be used alone or with other medications to treat chronic angina (ongoing chest pain or pressure that is felt when the heart does not get enough oxygen). A new stability indicating RP-UFLC method has been proposed for the quanification of Ranolazine in pharmaceutical formulations. Shimadzu Model CBM-20A/20 Alite high performance liquid chromatography system with PDA detector and Agilent C18 column were used for the chromatographic study. Materials and Methods: Mobile phase mixture consisting of tetra butyl ammonium hydrogen sulfate and methanol (47:53, v/v) with flow rate 0.8 mL/min was selected for the chromatographic study of Ranolazine with detection wavelength 215 nm. Results and Discussion: Ranolazine has shown linearity over the concentration range of 0.1â€“50 Î¼g/ml with linear regression equation, y = 71784x + 4994.2 (RÂ² = 0.9999). The LOD and LOQ were found to be 0.0319 Î¼g/ml and 0.0981 Î¼g/ml, respectively. Stress degradation studies were performed by exposing Ranolazine to various stress conditions and the method was validated as per ICH guidelines.